El aprendizaje basado en proyectos, para el fortalecimiento de la identidad cultural en el área de Ciencias Sociales, de quinto de básica de la Unidad Educativa “Dr. Emilio Uzcátegui” durante el año lectivo 2022-2023 en la parroquia Cebadas del cantón Guamote. - Berrones Romero, Julissa Rocio (2024)
The Project Based Learning (PBL) is a constructivist strategy crucial in the teaching-learning process, as it promotes cognitive and social skills to solve everyday problems, it highlights the importance of strengthening cultural identity in the face of the various problems that affect the full development of the student, which is why this research aims to propose a didactic guide on project-based learning, The approach presented by the research was mixed, with a cross-sectional study, a propositional scope, with a non-experimental research design, since the existing variables are not manipulated, with respect to its population was established with a sample of 23 students and a teacher of fifth year of basic education; The survey and interview techniques were used. Two instruments were used for data collection: a questionnaire made up of 8 questions addressed to the students and an interview guide addressed to the teacher and made up of 6 questions. The data collected reveal negative attitudes of the students towards their cultural identity, such as detachment and lack of knowledge of the language. In addition, the teacher mentions the lack of use of PBL (project-based learning) due to pre-established activities and limited resources. The importance of proposing activities that strengthen cultural identity through cultural skills and values is emphasized.